BSEP and MDR3: Useful Immunohistochemical Markers to Discriminate Hepatocellular Carcinomas From Intrahepatic Cholangiocarcinomas and Hepatoid Carcinomas. (May 2016) - Fujikura, Kohei; Yamasaki, Takashi; Otani, Kyoko; Kanzawa, Maki; Fukumoto, Takumi; Ku, Yonson; Hirose, Takanori; Itoh, Tomoo; Zen, Yoh
Abstract : We herein examined the immunohistochemical expression of 2 hepatocyte-specific transporters (bile salt export pump [BSEP] and multidrug-resistance protein 3 [MDR3]) in hepatocellular carcinomas (HCCs, n=54), intrahepatic cholangiocarcinomas (n=34), combined hepatocellular and cholangiocarcinomas (n=23), and hepatoid carcinomas originated from extrahepatic organs (n=27) to compare their diagnostic values with those of arginase-1 (ARG1) and hepatocyte paraffin-1 (HepPar-1). BSEP was expressed in 91% of HCCs and MDR3 in 83%. Although their sensitivities were slightly lower than those of ARG1 (96%) and HepPar-1 (93%), the 2 transporters appeared to be more specific for HCCs. ARG1 and HepPar-1 were expressed in intrahepatic cholangiocarcinomas (9% and 6%) and hepatoid carcinomas (22% and 44%, respectively), whereas BSEP and MDR3 were entirely negative in these neoplasms, except for 1 case of BSEP-positive hepatoid carcinoma of the esophagus. The highly specific expression of BSEP and MDR3 in hepatocytes was recapitulated in additional examinations of combined hepatocellular and cholangiocarcinomas, in which the expression of the transporters was restricted to morphologically hepatocellular areas. In contrast, ARG1 and HepPar-1 were also variably positive in areas of biliary or indeterminate differentiation. We also applied BSEP and MDR3 immunohistochemistry to 8 biopsy cases of poorly differentiated primary liver cancer, in which the original diagnosis was not conclusive. The diagnosis of HCC was retrospectively suggested in 2 cases expressing both BSEP and MDR3. In conclusion, given the highly specific expression of BSEP and MDR3 in HCCs, immunohistochemistry for these transporters will be useful not only for determining hepatocellular differentiation in primary liver cancers but also for discriminating HCCs from hepatoid carcinomas.